If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6c + 2 + -5c = -24 + 8 Reorder the terms: 2 + 6c + -5c = -24 + 8 Combine like terms: 6c + -5c = 1c 2 + 1c = -24 + 8 Combine like terms: -24 + 8 = -16 2 + 1c = -16 Solving 2 + 1c = -16 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 1c = -16 + -2 Combine like terms: 2 + -2 = 0 0 + 1c = -16 + -2 1c = -16 + -2 Combine like terms: -16 + -2 = -18 1c = -18 Divide each side by '1'. c = -18 Simplifying c = -18
| 9y+12x=294 | | -1/4(12x-20y) | | 6x10^4/3x10^2 | | x+1x-30=Y | | A^2-15a-54=0 | | A^3b^-5/A^-5b^3 | | 10.00+.10m=.35m | | 2n^2+2n-7=0 | | 2x+13=52 | | 11-2(3b+1)= | | 170+x=-340 | | 1.8a=6+2.25a | | -6x=2y+3 | | 4y=0x+28 | | 49=6x+13 | | 99-m=299 | | 6x=-2y-3 | | -6x=-2y-3 | | 37=6x+13 | | -4/x^2x=1/x-2 | | -51x=65 | | -51x=62 | | x-9+2x=12 | | (5)/(9)a=6+(4)/(9)a | | 5/7*42 | | 10-1(x+5)+3x=6x-5(x-1)-3 | | .02-.05+.3x=-.68 | | 68-60x=82 | | 14z-5=2z-65 | | 1/5(10x-1)=5 | | -16x=-256 | | p=-0.5x^2+16-12 |